Intellect and intellectual practices in the digitalized world: review of the 5th International scientific conference “Interdisciplinarity in the modern social-humanitarian knowledge - 2020 - E. Yu. Bazhenova (Russian Journal of Economics and Law)
Objective: to familiarize a wide range of the Journal readers with the results of the “Interdisciplinarity-2020” conference and the new ideas and research results presented in the reports of Russian and foreign scientists focused on the problem of intelligence in the digital world. Methods: a systematic approach to the cognition of social phenomena has determined the use of the following research methods: analysis, synthesis, comparison, structural and functional methods, content analysis.Results: the content of the main reports presented at the international scientific event is described (by G. B. Kleiner, D. V. Ushakov, R. M. Nureyev, E. V. Balatsky, S. G. Kirdina-Chandler and other researchers), which analyze various aspects of the functioning and development of intelligence in the digital world, the types and levels of intelligence, and the impact on socio-economic processes. The speakers presented various views on the processes of digital transformation of the economy and society, including the analysis of the main risks of implementing a digital project in Russia in terms of its impact on economic growth in the context of global political and economic trends. The thesis is formulated about the inevitability of the transition to a new type of economy - the intellectual economy, in which knowledge is the subject, and intelligence is the means of labor. Speakers from interdisciplinary positions hightlighted a number of urgent fundamental scientific problems that need to be solved: the creation of intellectual economy institutions; the change of the legal environment; the formation of a legal system that ensures the functioning of intellectualized sociotechnical systems. The complex of problems and tasks in the field of higher education aimed at the formation of intellectual competencies for the digital world is considered, the role and position of universities in the modern world are assessed. Scientific novelty: interdisciplinarity as one of the current trends in the development of scientific knowledge about man, nature and society is aimed at overcoming the fragmentation of disciplinary knowledge to ensure the effectiveness, consistency and harmony of social management and design. The novelty of the problems discussed at the conference was due to a special focus - “Intelligence in the digital world: influence, management, development”. Intelligence is considered as the main means of achieving social goals at both macro-, meso- and microsocial levels. The reports presented in the article are focused on a comprehensive analysis of the key factors of socio-economic and humanitarian development, the most important of which today are knowledge and intelligence. The scientific novelty of the discussed problems lies in the totality of the object, subject and research methods: a comprehensive analysis of intelligence in the modern digital world; expansion of the semantic content of this concept; the analysis of the phenomena of various types of intelligence interweaving (natural, artificial, social), based on an interdisciplinary approach; and uniting the efforts of economists, sociologists, linguists, philosophers, lawyers, historians, as well as representatives of technical branches of knowledge.Practical significance: the main provisions and conclusions of the review can be used in scientific and educational activities to improve the level and quality of information interaction when implementing interdisciplinary practices of the academic community, to identify and disseminate the best practices of interdisciplinary research, as well as to improve the management and planning of innovation activities of academic organizations, evaluation and expertise of research activities.